(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Dermatoglyphics is one the vital tool which helps to predict many systemic diseases including oral problems. Dental caries seems to be a major problem overall the globe. The best way to manage this condition is only early diagnosis. Aim: This study aims to assess whether dermatoglyphics effective in predicting dental caries. Materials and Method: A systematic review of controlled trials was performed. The data were hand searched using electronic databases and the 328 number of articles were screened. The intervention and outcomes were assessed in the study included for systematic review. The bias assessment of the articles was done by using Newcastle Ottowa scale. Results: Seventeen cross-sectional studies were included in our systematic reviews. Of that sixteen articles were found to be statistically significant, but further studies should be done in other countries to prove the association between dermatoglyphic pattern and dental caries. Conclusion: The pattern of dermatoglyphics was found to be very effective in predicting dental caries and thereby prevent the caries formation at an incipient stage.